The Influence of Clarity of Budget Targets, Implementation of Accounting Systems, and Internal Control on Accountability of Village Fund Management - Zian Addi Nana; Ernawati Budi Astuti; Hasan Velayati (Universal Business and Management Review, 2025)
This study aims to determine the effect of budget target clarity, accounting system implementation, and internal control on village fund management accountability. This study uses a quantitative approach using primary data from Kragan District, Rembang Regency, Central Java, Indonesia. The sample used in the study was 80 village officials. The collection method was a questionnaire with a Likert scale measurement. The data analysis technique used was multiple linear regression with the help of SPSS software. The results indicate that budget target clarity, application of the accounting system, and internal control have a positive and significant effect on village fund management accountability. This study concludes that budget targets, implementation of accounting systems, and internal control have a positive contribution to the level of accountability in managing village funds.